INNOVATIVE LEARNING MODEL WITH INCLUSIVE-COLLABORATIVE APPROACH FOR STUDENTS WITH SPECIAL NEEDS - Fermanto Lianto; Nafiah Solikhah; Andi Surya Kurnia; Franky Liauw; Margaretha Syandi; Caroline Sunjaya Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
In order to face the era of technological disruption and the industrial revolution 4.0, it is necessary to improve the curriculum and educational methods for the Bachelor of Architecture that is friendly for disabilities. Therefore, it is necessary to innovate, research, and apply online and digital technology, architectural computing systems that can be utilized optimally in XYZ University’s architectural education model. Architectural education must be sensitive and do self-introspection so that it can detect its position during the rapid development of science and technology. Specialized classroom design includes seating position, layout, optimized space, and usage of special computer applications to help students with disabilities in the study and learning process. The methodology approach used Descriptive, experimental, and quantitative methods based on an interdisciplinary approach centralized on psychological methods and designing facilities that support the learning process. The research resulted in designating a position in the classroom that is ideal for a student with disabilities. This position helps them to participate in the classroom efficiently. Equipment such as speakers and an LED TV is placed to help people with disabilities. Transcription software is used to transcribe lecturers in real-time. This research was conducted with the use of compatible software to get optimal results. Several methods and tools are used to support this research to obtain optimal results for the learning process, especially for people who are deaf or have low vision. Audio and visual aspects are prioritized without neglecting other supporting aspects. Dalam rangka menghadapi era disrupsi teknologi dan revolusi industri 4.0, perlu dilakukan penyempurnaan kurikulum dan metode pendidikan Sarjana Arsitektur yang ramah bagi disabilitas. Oleh karena itu perlu dilakukan inovasi, riset, dan menerapkan teknologi online dan digital, sistem komputasi arsitektural yang dapat dimanfaatkan secara optimal dalam model pendidikan arsitektur Universitas XYZ. Pendidikan arsitektur harus peka dan melakukan introspeksi diri sehingga mampu mendeteksi posisinya di tengah perkembangan ilmu pengetahuan dan teknologi yang begitu cepat. Desain ruang kelas khusus mencakup posisi tempat duduk, tata letak, ruang yang dioptimalkan, dan penggunaan aplikasi komputer khusus untuk membantu siswa penyandang disabilitas dalam proses belajar dan belajar. Pendekatan metodologi yang digunakan adalah metode Deskriptif, eksperimental, dan kuantitatif berdasarkan pendekatan interdisipliner, terpusat pada metode psikologis dan merancang fasilitas yang mendukung proses pembelajaran. Penelitian ini menghasilkan penunjukan posisi di kelas yang ideal bagi siswa penyandang disabilitas. Posisi ini membantu mereka untuk berpartisipasi di dalam kelas secara efisien. Perlengkapan seperti speaker dan TV LED ditempatkan untuk membantu para penyandang disabilitas. Software transkripsi digunakan untuk mentranskripsi dosen secara real-time. Penelitian ini dilakukan dengan menggunakan software yang kompatibel untuk mendapatkan hasil yang optimal. Beberapa metode dan alat digunakan untuk mendukung penelitian ini agar mendapatkan hasil yang optimal untuk proses pembelajaran, terutama bagi penyandang tunarungu atau low vision. Aspek audio dan visual diprioritaskan tanpa mengabaikan aspek pendukung lainnya.